Bioética e direitos humanos: diagnóticos e proposições sobre saúde com enfoque nos transplantes de diversos órgãos post mortem no Tocantins - Ribeiro, Daniel de Paula Silva (Universidade Federal do Tocantins, 2020)
This dissertation aims analyze the role of the Judiciary in the politicization of life, or biopolitics, more precisely in guarantee the right to health. Through the conceptual and principiological contributions of bioethics and human rights, the phenomenon of the judicialization of politics is seen as a way to guarantee social rights, above all, the right to health is inseparable from the right to life and the dignity of the human person. Thus, it seeks to observe this phenomenon in the Brazilian reality, especially in the state of Tocantins, also proposing discussions about access to health through organ and tissue transplants. Therefore, the methodological approach is based on a deductive approach, historical-comparative procedures and a case study, and the mostly used research technique is qualitative, with literary reviews and documentary analysis. It seeks to demonstrate in its results the positive and negative points of the interference of the judicial policy in the health area, evidencing its importance in protection of the life and dignity of the human person, but due to the need to equalize its actions with the entities and institutions policies.